2007
DOI: 10.1159/000098961
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Sequences of Two Hepatitis E Virus Isolates Representing an Eastern China-Indigenous Subgroup of Genotype 4

Abstract: Although the majority of hepatitis E virus (HEV) infections in Japan are ‘domestic’ due to the presence of indigenous strains, there are still ‘imported’ cases as well. Among 83 patients with non-A, non-B and non-C acute liver diseases admitted to Saitama Medical University Hospital, 7 (8.4%) were positive for serum HEV-RNA, of whom 2 had a recent history of traveling to China, one to Xian and another to Shanghai. We determined the full-genome sequences of HEV from these 2 patients (isolate names are JKO-ChiSa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Koike et al. (2007) isolated a genotype 4 HEV strain () from a Japanese patient who had history of travelling to Shanghai City of China and suggested that this isolate was Shanghai‐indigenous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koike et al. (2007) isolated a genotype 4 HEV strain () from a Japanese patient who had history of travelling to Shanghai City of China and suggested that this isolate was Shanghai‐indigenous.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that these isolates came from a common origin and supported that zoonotic transmission of HEV was involved in Shanghai region. Koike et al (2007) isolated a genotype 4 HEV strain (EF197674) from a Japanese patient who had history of travelling to Shanghai City of China and suggested that this isolate was Shanghai-indigenous. We included this isolate in our sequence analysis and results indicated that it had not close relationship to any isolates we determined in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis (Fig. 2 ) based on full OFR2 sequences indicated the isolate in the present study shared 87.2–97.6% identities with the other Chinese genotype 4 HEV isolates referenced here, and the highest sequence identity (97.6%) with another Shanghai HEV strain ( AB197674 ) isolated from a Japanese patient who was reportedly infected during traveling in Shanghai of China [ 8 ]. Phylogenetic analysis indicated that the isolate determined in this study closely clustered with other 3 Chinese genotype 4 HEV strains from human (Fig.…”
Section: Resultsmentioning
confidence: 93%